Brain segmentation unmasks association between body composition and central nervous system structures - Katulska, Katarzyna; Wykrętowicz, Mateusz; Piskorski, Jarosław (Journal of Medical Science, 2014)
Introduction. Excess body fat is currently the major health problem. We suggest that marker of fatness like BMI or percent of body fat are associated with gray matter volume (GMV) or brain areas responsible for cognitive functions.Material and methods. Study was performed in 89 healthy individuals (mean age 58 yrs, 51 women). For brain segmentation and GMV we used whole-brain, high-resolution 3D T1-weighted images. For assessment of the fat content as a proportion of total body mass a bio-impedance analyzer was used. Result. GMV was correlated, significantly and negatively with age but was not associated either with BMI nor body fat content. Body fat content was significantly and negatively associated with hippocampus and thalamus.Conclusion. We demonstrate that brain segmentation was able to unmask the association between body fat content and brain structures particularly involved in cognitive function.